THE DEVELOPMENT OF OSILATIONS AND WAVES SIMULATION IN SCIENCE EDUCATION FOR JUNIOR AND SENIOR HIGH SCHOOL - Yennita Yennita; Ahmad Ma’ruf; Nisa Ul Husni; Hendar Sudrajat; Zulirfan Zulirfan (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2017)
Science education must be involved in direct experience. Therefore, student must study with finding problem method not talkative method. Education’s module about vibration and wave in curriculum demand, must be accomplish with experient. Unfortunately, this method are difficult to use because the lack of experient tools to produce measured standing waves like velocity, amplitude, period and frequency. The purpose of this research to develop vibration’s simulation experiement tool. This research are belong to developing research type, because it was used to producing some products, and testing the effectiveness of a product. The experiment was following ADDIE model steps, which were consist of 5 steps to follow such as analysis, design, development, implementation and evaluation. The experiment tools could be used after validated by the expert. After the validation finished, the tools can be tested in the field. The validation result from experiment tools and Student Worksheets already passed the validation from the experts. After tested in the student’s groups, the result were positive and fulfill the criteria practical from students view. Therefore, the tools can be used widely to see its effectiveness.